Wear Surface Studies on Ejector-nozzle in Circulating Fluidized-Bed Gasifier. Issue 6 (26th April 2022) - Liu, Xiaoying; Chen, Zhichao; Li, Liankai; Li, Zhengqi; Zeng, Lingyan
ABSTRACT: A key component of a circulating fluidized-bed gasifier is the recycling control device, which is important for stable solid circulation and combustion of particles. In our previous work, a steam–solid ejector was used as a recirculating control device to provide a continuous and stable pressure barrier, which reduced the amount of unburned combustibles in the fly ash. Damage to the ejector nozzle seriously affected the combustion stability and effective syngas concentration. The causes of wear of the nozzle surface were analyzed using a combination of methods. Computational fluid dynamics showed that the radial velocity near the nozzle zone approached 10–12 m/s and obvious erosion appeared on the surface of the nozzle. Scanning electron microscopy and energy-dispersive spectroscopy indicated that the direction of grooves that appeared on the worn nozzle surface was the same as that of the gas–solid flow and that the Ni-based structure of the original material was seriously damaged.